Efektivitas Komunikasi Organisasi dalam Perspektif Islam di Lembaga Pendidikan - Khairani, Khairani; Simanjuntak, Siti Khalijah; Sulasmi, Sulasmi; Chair, Sultan Ayughi; Mesiono, Mesiono (EduInovasi: Journal of Basic Educational Studies, 2024)
The focus of this research is on organizational communication in the perspective of Islamic education that has not been effective. By using relevant literature and references, this research determines the importance of communication in Islamic educational organizations. Data was collected through Google Scholar. Verses from the Qur'an are used to illustrate the role of communication within an organization. When members of the organization know how to communicate well, then organizational communication can run smoothly. Effective communication among organization members maintains good relationships in accordance with established rules. The verses from the Qur'an serve as a basis for communication within the educational institution. This study found that communication among organization members using hierarchical positions should be well-established and consider the tasks and positions of each.